Proceedings of the 2002 International Symposium on Symbolic and Algebraic Computation 2002
DOI: 10.1145/780506.780528
|View full text |Cite
|
Sign up to set email alerts
|

Factoring zero-dimensional ideals of linear partial differential operators

Abstract: We present an algorithm for factoring a zero-dimensional left ideal in the ringQ(x, y)[∂x, ∂y], i.e. factoring a linear homogeneous partial differential system whose coefficients belong toQ(x, y), and whose solution space is finite-dimensional overQ. The algorithm computes all the zero-dimensional left ideals containing the given ideal. It generalizes the Beke-Schlesinger algorithm for factoring linear ordinary differential operators, and uses an algorithm for finding hyperexponential solutions of such ideals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…In a series of publications Li, Schwarz and Tsarev [36][37][38] considered such systems of pde's in the plane and showed that a theory similar as for the ordinary case may be developed.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of publications Li, Schwarz and Tsarev [36][37][38] considered such systems of pde's in the plane and showed that a theory similar as for the ordinary case may be developed.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there has been work on decomposing these systems into "subsystems" whose solution spaces are of lower dimension. This has been done following either ideal-theoretical [16,17] or module-theoretical [2,21] approaches. In both cases the methods require the computation of hyperexponential solutions of some linear functional systems obtained from either the associated equations or the integrable systems [20].…”
Section: Introductionmentioning
confidence: 99%
“…By factoring the differential modules associated with systems of linear PDE's with finitedimensional solution spaces, the algorithm FactorDiffMod improves the factorization algorithm in [6]. Further work will include the refinement of the step in the algorithm OneDimSubMods which deals with computing hyperexponential solutions of integrable systems and the improvement for computing ranks of parameterized matrices.…”
Section: Discussionmentioning
confidence: 99%
“…We now apply the algorithm FactorDiffMod to redo Example 1 in [6]. To compute two-dimensional submodules of M , construct the second exterior power ∧ 2 M of M with a basis {f 1 := e 1 ∧ e 2 , f 2 := e 1 ∧ e 3 , f 3 := e 2 ∧ e 3 } and compute the integrable system associated with ∧ 2 M :…”
Section: Factorization Algorithmmentioning
confidence: 99%
See 1 more Smart Citation